The Jewish state : a century later - Dowty, Alan, 1940- (University of California Press, 1998)
The Jewish State is a comprehensive interpretative study of the historical roots and contemporary functioning of Israel. Nationhood and democracy have not unfolded in a social or political vacuum, but instead developed from pre-state Jewish traditions in Palestine and in Eastern Europe. Dowty elucidates a broad cluster of cultural, historical, and ideological tenets that have come to comprise the infrastructure of the contemporary political system. His analysis provides a new interpretation of the formation and development of the Israeli nation. This book will prove invaluable for students, scholars, and general readers looking for one book that will give them an intelligent overview of the Jewish state.
Keywords: Israel -- Politics and government.; Democracy -- Israel.; Jews -- Politics and government.; Democracy -- Religious aspects -- Judaism.; Judaism and state -- Israel.; Jews -- Israel -- Identity.; Zionism -- History.; Palestinian Arabs -- Israel -- Politics and government.; Israël -- Politique et gouvernement.; Juifs -- Politique et gouvernement.; Judaïsme et État -- Israël.; Juifs -- Israël -- Identité.; POLITICAL SCIENCE -- Political Process -- General.; Democracy; Democracy -- Religious aspects -- Judaism; Jews -- Identity; Jews -- Politics and government; Judaism and state; Palestinian Arabs -- Politics and government; Politics and government; Zionism; Israel; Government - Asia.; Government - Non-U.S.; Law, Politics & Government.; History